Ответ:
(a-x)^3 + (b-x)^3 - (a+b-2x)^3 = 0 a^3 - 3a^2x + 3ax^2 - x^3 + b^3 - 3b^2x + 3bx^2 - x^3 - (a^3 + 3a^2b - 6abx + 6ax^2 + b^3 - 6ab^2 + 12bx^2 - 8x^3) = 0 -6ax^2 - 6bx^2 + 12ax^2 + 12bx^2 - 8x^3 + 2x^3 = 0 -6x^3 = 0
Отже, розв’язком цього рівняння є x = 0.
Объяснение:
Автор:
foxychandlerДобавить свой ответ
Предмет:
ЛитератураАвтор:
pookie6weuОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
odónhhquОтветов:
Смотреть
Предмет:
Українська літератураАвтор:
supermanОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
makennaburkeОтветов:
Смотреть